2019
DOI: 10.1080/0144929x.2019.1636136
|View full text |Cite
|
Sign up to set email alerts
|

Digital inclusion of people with disabilities: a qualitative study of intra-disability diversity in the digital realm

Abstract: This paper presents an in-depth study of intra-disability diversity in the digital realm and the related role of individuality and selectiveness in the digital choices and experiences of people with disabilities (PwD). The study adopts the interactionist model of disability and problematises conceptual uniformity in research that focuses on the medical and socially-constructed features of disability as those determining digital constraints and affordances for PwD. Through primary qualitative evidence, it argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 78 publications
1
23
0
2
Order By: Relevance
“…According to Tsatsou, creating opportunities for digital inclusion is critical especially with digital technologies potentially amplifying complex inequalities ( 12 ). These complexities include how different communities access technologies, use them, and benefit from them.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tsatsou, creating opportunities for digital inclusion is critical especially with digital technologies potentially amplifying complex inequalities ( 12 ). These complexities include how different communities access technologies, use them, and benefit from them.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-disability and intersectional diversity importantly intersect with digital media use. PWDs are sometimes treated as a homogeneous group, although their experiences can be highly divergent (Tsatsou, 2019); research at schools has, indeed, identified different groups of pupils, such as a majority feeling excluded and a small minority having close friendships, reinforced digital media use (Asbjørnslett et al, 2011; Söderström, 2009). Our study highlights three issues.…”
Section: Discussionmentioning
confidence: 99%
“…The social inclusion of PWDs usually refers to PWDs being accepted by peers, both able-bodied and those with different disabilities, bearing in mind intra-disability diversity (Goggin, 2017b; Tsatsou, 2019). Furthermore, social inclusion refers to both interpersonal relationships and community participation (e.g.…”
Section: Social Inclusion and Digital Mediamentioning
confidence: 99%
“…Conforme os dados do último levantamento realizado pela Organização Mundial de Saúde (World Health Organization, 2012) mais de um bilhão de pessoas em todo o mundo possuem algum tipo de deficiência, o que equivale a cerca de 15% da população global (Domínguez Vila, Darcy, & González, 2015;Tsatsou, 2019). Tais dados, corroborados pelo potencial crescimento da população idosa (que frequentemente apresenta dificuldades de mobilidade, visão e audição) tem culminado em diversos estudos referentes ao turismo para pessoas com deficiência ou mobilidade reduzida (chamado de turismo acessível), que tem sido apontado por vários autores como um rentável nicho de mercado (Huh & Singh, 2007;Babaita, 2012;Williams et al, 2017;Rabontu, 2018 (Zbikowski, Kuzmicki, Dabrowski, & Soroka, 2011).…”
Section: Introductionunclassified
“…Entretanto, há que se observar a importância da informação em todo o processo de viagem da PcDMr, seja como canal de comunicação ou como compartilhador de experiências (Domínguez Vila et al, 2018a), sendo também importante observar que em virtude da ainda reinante exclusão das pessoas com deficiência (PcD), tem crescido o interesse dos pesquisadores em investigar de que forma as tecnologias e serviços digitais podem influenciar na qualidade de vida para a PcD (Tsatsou, 2019).…”
Section: Introductionunclassified